On intuition in decision-making - Vergara, Sylvia Constant (1993)
This is an article based on bibliographical and empirical research, the latter made alongside managers of complex organizations and other professionals. lt deals with statements and references that have been sought in other realms of knowledge out of Public Administration, in order to elucidate what is intuition, if an intuitive decision necessarily leads to the expected results and if it is possible to develop intuition. The contention is positive and several suggestions are offered to achieve that development. lt is also argued that intuition transcends reason and that both are present in the decision-making process.